Local Wisdom-Based Ecotourism Development Model In Sambangan Village, Sukasada District, Buleleng Regency Bali province - Toto Noerasto; Ayu Dewi Larantika; I Made Mardika; Ni Luh Sephia Adnyani Putri (Cita Konsultindo Research Center, 2024)
This study aims to analyze the model of ecotourism development based on local wisdom in Sambangan Village, Sukasada District, Buleleng Regency, Bali Province, and identify the role of local wisdom in managing ecotourism. Sambangan Village holds significant ecotourism potential with its natural attractions like Aling-Aling Waterfall, as well as unique local culture and arts. However, the development of ecotourism in this village has been hindered by the lack of appropriate strategies and limited community involvement in maximizing its potential. This research employed a qualitative method with data collection techniques including observation, interviews, documentation, and Focus Group Discussions (FGD). Data analysis followed the stages outlined by Miles, Huberman, and Saldana, which involved data collection, data reduction, data presentation, and conclusion drawing and verification. The findings showed that the ecotourism development model in Sambangan Village involved the integration of natural, cultural, and artificial tourism. Local wisdom, such as the spirit of community cooperation (gotong royong) and cultural preservation, plays a vital role in ecotourism management. The community actively participates through institutions like LPHD and POKDARWIS, engaging in sustainable tourism management. Furthermore, infrastructure improvements and accessibility enhancements were needed to support further development. Diversification of tourist attractions and improving community skills through training programs were also recommended to increase the village's appeal as a leading ecotourism destination.